2007
DOI: 10.1128/jvi.00766-06
|View full text |Cite
|
Sign up to set email alerts
|

Human T-Cell Leukemia Virus Type 1 Tax Protein Down-Regulates Pre-T-Cell Receptor Alpha Gene Transcription in Human Immature Thymocytes

Abstract: The human pre-T-cell receptor alpha (TCR␣; pT␣) gene encodes a polypeptide which associates with the TCR␤ chain and CD3 molecules to form the pre-TCR complex. The surface expression of the pre-TCR is pT␣ dependent, and signaling through this complex triggers an early ␣␤ T-cell developmental checkpoint inside the thymus, known as ␤-selection. E2A transcription factors, which are involved at multiple stages of T-cell development, regulate the transcription of the pT␣ gene. Here we show that the regulatory protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 46 publications
3
16
0
1
Order By: Relevance
“…1D). In agreement with a previous study (45), the amount of pT␣ mRNA was strongly reduced under similar conditions (Fig. 1E).…”
Section: Vol 82 2008supporting
confidence: 81%
See 3 more Smart Citations
“…1D). In agreement with a previous study (45), the amount of pT␣ mRNA was strongly reduced under similar conditions (Fig. 1E).…”
Section: Vol 82 2008supporting
confidence: 81%
“…The HTLV1-LTR-luc was kindly provided by A. Rabson (27). pJFE-Tax WT, M22, M47, and K88A were previously described (45). Plasmid pSUPER-TAL1 was generated by annealing the oligonucleotides 5Ј-GATCCCCGAAGCTCAGCAAGAATGAGCTC TTCCTCCTCATTCTTGCTGAGCTTCTTTTT-3Ј and 5Ј-AGCTAAAAAG AAGCTCAGCAAGAATGAGGAGGAAGAGCTCATTCTTGCTGAGCT TCGGG-3Ј and inserting the resulting DNA fragment between the BglII and HindIII restriction sites of pSUPER (6).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…That is to say the immune response of HBV will be reduced if mutations occur in the TCR [11][12][13][14][15][16][17][18][19] . Some studies have indicated that the priority expression and employment of TCR were related with the specific immune reaction of chronic hepatitis B [20][21][22][23][24][25][26][27] . In our study of the object, we discovered that the growth rates of leukomonocyte were difference among the patients who bring A121T, C139S mutation, normal controls and common pancreatitis patients and the growth rate of leukomonocyte of the patients who bring A121T and C139S mutation was comparatively low and that the CD4⁄CD8 proportionality was degraded.…”
Section: Discussionmentioning
confidence: 99%